2004
DOI: 10.1103/physreva.70.022307
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an interaction and entanglement between distant atoms

Abstract: We propose a scheme to generate an effective interaction of arbitrary strength between the internal degrees of freedom of two atoms placed in distant cavities connected by an optical fiber. The strength depends on the field intensity in the cavities. As an application of this interaction, we calculate the amount of entanglement it generates between the internal states of the distant atoms. The scheme effectively converts entanglement distribution networks to networks of interacting spins.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 30 publications
0
74
1
Order By: Relevance
“…This model might describe an electron spin weakly coupled to stable a nuclear spin. The same model was derived for two atoms in separate cavities connected by optical fibers (Fig 5) in the large-detuning regime [30,31]. In the latter case we could achieve γ 2 γ 1 by choosing different Q factors for the two cavities so that on certain time scale that one atom experiences spontaneous decay while the other does not.…”
Section: Invariant Set Of Dynamics Decoherence-free Subspacesmentioning
confidence: 96%
“…This model might describe an electron spin weakly coupled to stable a nuclear spin. The same model was derived for two atoms in separate cavities connected by optical fibers (Fig 5) in the large-detuning regime [30,31]. In the latter case we could achieve γ 2 γ 1 by choosing different Q factors for the two cavities so that on certain time scale that one atom experiences spontaneous decay while the other does not.…”
Section: Invariant Set Of Dynamics Decoherence-free Subspacesmentioning
confidence: 96%
“…Then, in the short fiber limit (2Lν)/(2πc) ≪ 1, where L is the length of fiber andν is the decay rate of the cavity field into a continuum of fiber modes, only the resonant mode of the fiber will interact with the cavity modes. For this case, the interaction Hamiltonian of cavity-fiber can be written as [53] …”
Section: (B)mentioning
confidence: 99%
“…On the other hand, it has been shown that entanglement and QST between spatially separated quantum nodes is very useful for distributed quantum computation [53] and quantum network [54,55]. In recent years, a large number of schemes have been proposed for generating entanglement and QST between spatially separated atoms, which are individually trapped into distant optical cavities connected by fibers (i.e., cavity-fiber-cavity system) [56][57][58][59][60][61].…”
mentioning
confidence: 99%
“…The coupled electron spins of the neighboring phosphorus atoms serve as the static "quantum bus" which transfers the interaction between nearestneighbor and distant nuclear spins in a chain with more than two phosphorus atoms. In a similar technique "flying" qubits represented by photons has been proposed to mediate the qubit-qubit interaction between trapped ions [11,12,13,14,15,16,17].…”
Section: Hamiltonianmentioning
confidence: 99%